The History of the Writer Oybek`S HouseMuseum in Tashkent and it`S Importance in the Cultural Life of Society - Elmuratova Shokhista Ablakulovna (Western European Studies, 2023)
The history of the Oybek House-Museum, which is currently operating in Tashkent, has been studied in the following article. Because most of the existing house-museums in our country aresituated in Tashkent, this paper stresses on studying the history and activities of the house-museums in this region
Keywords: Museum; society; person